Non-radiative processes in deep centres of diamond - Pereira, E.
The N3 centre in diamond is shown to have delayed luminescence above 170 K, following excitation into the N3 absorption band and at all temperatures for excitation into the N4 absorption band. At low temperatures a new slow luminescing band of vibronic origin is observed. The results give independent evidence of the metastable states found in the N3 centre by other methods.